ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PENGANGKUTAN SAMPAH DI KELURAHAN NAWARIPI KABUPATEN MIMIKA - Elisabet Narut; Yulita Yuliana Jawa Kasi; Muhamad Sabir (CV. ADIBA AISHA AMIRA, 2026)
This study aims to determine community satisfaction with waste collection services in the Nawaripi sub-district. The method used in this study is a descriptive quantitative approach with a questionnaire as the data collection instrument and the Community Satisfaction Index as the analysis tool, with results presented in numerical form. The results of this study show that the community satisfaction index (CSI) for waste transportation services in Nawaripi sub-district is 2.39 with a conversion score of 59.75, indicating that the performance of waste transportation services in Nawaripi sub-district is in the category of poor service quality.